Postoperative chest liver herniation after cardiophrenic lymph node resection by a transdiaphragmatic approach following primary cytoreductive surgery for advanced endometrioid ovarian cancer: A case report - Hélène Leray; Laurent Brouchet; Yann Tanguy Le Gac; Sihem Bouharaoua; Philippe Otal; Gwenaël Ferron; Erwan Gabiache; Martina Aida Angeles; Carlos Martínez-Gómez; Alejandra Martinez (Elsevier, 2021)
Resection of enlarged cardiophrenic lymph nodes (CPLN) is a procedure required to obtain complete cytoreduction in selected patients affected by advanced ovarian cancer. Their resection by transdiaphragmatic approach has been demonstrated to be feasible with low rates of morbidity. The main complications associated with this procedure are pleural effusion, pneumothorax, and rarely, chylothorax.This case describes a postoperative chylothorax and chest liver herniation in a patient who underwent a cytoreductive surgery for advanced endometrioid ovarian cancer, which included a right transdiaphragmatic CPLN resection. Surgical management by thoracotomy was required to repair the right diaphragmatic defect combined with conservative management of the chylothorax. The diaphragmatic closure was achieved employing interrupted stitches with a non-absorbable suture. No prosthetic material was required.